2017
DOI: 10.1093/humrep/dex072
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1–7) in human follicular fluid correlates with oocyte maturation

Abstract: Research supported by Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq) and Fundação de Amparo à Pesquisa do Estado de Minas Gerais (FAPEMIG). The authors have nothing to disclose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 32 publications
3
28
0
Order By: Relevance
“…A series of immune cytokines have been identified differentially expressed in the FF of PCOS women (6,7). Furthermore, cytokines, growth factors, proteins, metabolites, and microRNAs found in FF have been associated with oocyte competence, while angiotensin-(1-7) levels in human FF have been correlated with oocyte maturation (8,9). Impaired oocyte quality and outcomes of in-vitro fertilization (IVF) in PCOS have been linked to changes in the components of FF, yet the mechanisms have not been fully elucidated (7, 10).…”
Section: Introductionmentioning
confidence: 99%
“…A series of immune cytokines have been identified differentially expressed in the FF of PCOS women (6,7). Furthermore, cytokines, growth factors, proteins, metabolites, and microRNAs found in FF have been associated with oocyte competence, while angiotensin-(1-7) levels in human FF have been correlated with oocyte maturation (8,9). Impaired oocyte quality and outcomes of in-vitro fertilization (IVF) in PCOS have been linked to changes in the components of FF, yet the mechanisms have not been fully elucidated (7, 10).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies describe RAS as a complex system arranged on two main axes: one represented by the ACE/ANG II/ANG I receptor, and the other ACE 2/ANG 1-7/MAS receptor (26). The intermediate products ANG 1-7 have been shown to be biologically active, which renders it more difficult to quantify the process and to manage and control this system with appropriate medication (27). This study is, to the best of our knowledge, one of the first studies in our country showing elevated ANG II levels in the follicular fluid collected from OHSS patients.…”
Section: Discussionmentioning
confidence: 99%
“…also profiled miRNA expression using aortic tissues from 8 AAAD patients and 9 controls, they showed that 33 miRNAs was upregulated and 8 miRNAs was significantly downregulated (>2-fold). However, only the upregulation of miR-21-5p was validated by RT-PCR 35 . Moreover, aberrant upregulated miR-30a and decreased miR-124 was also observed in the aortic tissue of AAAD patients 36 , 37 .…”
Section: Discussionmentioning
confidence: 99%